The role of dietary sugars in cancer risk: A comprehensive review of current evidence - Nazmul Hasan; Omid Yazdanpanah; Barbod Khaleghi; David J. Benjamin; Arash Rezazadeh Kalebasty (Cancer Treatment and Research Communications)
Goal of the review: The objective of this review is to conduct a thorough examination of the current evidence regarding the correlation between dietary sugar intake and cancer risk. This will encompass the biological mechanisms, the diverse effects of various sugar types, and the potential implications for cancer treatment and dietary recommendations. Introduction: Nutritional and epidemiological studies now focus much on the relationship between sugar intake and cancer. The data is still conflicting even if some studies imply that excessive sugar intake can help cancer develop by means of insulin resistance and chronic inflammation. Discussion: Through processes such as insulin resistance, inflammation, and angiogenesis, dietary sugars can impact carcinogenesis. Fructose increases angiogenesis by VEGF overexpression while glucose stimulates cancer cell growth by the Warburg effect. Contradicting data on the contribution of sugar to cancer emphasizes the need of consistent research techniques to simplify these dynamics. Reducing added sugar consumption in cancer prevention and management is especially crucial given that sugar affects immune function and treatment resistance, which could lead to new therapeutic targets. Conclusion: High sugar intake is linked to mechanisms such as the Warburg effect, insulin resistance, and chronic inflammation, which may contribute to cancer risk under specific conditions. However, the evidence is not universally conclusive, and additional large-scale, long-term research are required to better understand these processes. To help in cancer prevention and management, public health guidelines should emphasize reducing added sugar consumption and promoting a balanced diet rich in natural foods.